Patient Attributes and Trust in Physician - Pasch, Jenna; Treffert, Brianne; O'Brien, Michael (My University, 2012)
Research has shown that a patient's trust in his/her physician may affect their willingness to follow prescribed medical treatments, and therefore their overall health outcomes (Fiscella, Meldrum, Franks, Shields, Duberstein, McDaniel, Epstein, 2004). The patient-physician relationship is influenced by multiple sources; research has focused on characteristics of the physician (Duberstein, Meldrum, Fiscella, Shields, Epstein, 2007), but the patient's attitude and characteristics are also an essential contributor. This study examines patient self-esteem (Rosenberg, 1965), willingness to communicate (McCroskey& Richmond, 1985), the levels of perceived homophily (McCroskey, Richmond, & Daly, 1975) between the patient and physician, self-disclosure (Wheeless, 1978), and trust (Wheeless, 1977) in physician.
Color poster with text, images, and graphs.
Keywords: Posters; Trust; Attitude (Psychology)--Health aspects; Communication in medicine; Personality; Physician and patient; Patient compliance